1988
DOI: 10.1016/0042-6822(88)90285-1
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the PA protein gene of cold-adapted B/Ann Arbor/1/66 influenza virus associated with reversion of temperature sensitivity and attenuated virulence

Abstract: Reassortant SG3 inherits only the acidic polymerase (PA) protein gene from the cold-adapted B/AA/1/66 influenza virus (ca B/AA/1/66) and all remaining genes from a virulent, wild-type virus. This reassortant demonstrates attenuated virulence in ferrets and expresses a ts phenotype characteristic of the ca parent. During virulence evaluation of SG3, a virulent, non-ts revertant virus (designated SG3rFL) was isolated from the lungs of one ferret. In order to determine whether the reversion of SG3 resulted from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…38,39 The 6 internal genes of the LAIV-T parent attenuated strains provide the phenotypic characteristic of attenuation, cold adaptation, and temperature restriction. The polygenic nature and multiple gene mutations contained in the 6 internal genes contribute to the stability of the attenuated phenotype of LAIV-T. 40,41 The formation of new reassortants between LAIV-T and a contemporary interpandemic influenza virus would most likely yield attenuated to wild-type-like variants. Genetic reassortants during interpandemic periods do not seem to have a selective advantage.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 The 6 internal genes of the LAIV-T parent attenuated strains provide the phenotypic characteristic of attenuation, cold adaptation, and temperature restriction. The polygenic nature and multiple gene mutations contained in the 6 internal genes contribute to the stability of the attenuated phenotype of LAIV-T. 40,41 The formation of new reassortants between LAIV-T and a contemporary interpandemic influenza virus would most likely yield attenuated to wild-type-like variants. Genetic reassortants during interpandemic periods do not seem to have a selective advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ts phenotype of many experimental ts influenza viruses is unstable in vitro or in vivo (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), the ts phenotype of the caAA60-based vaccines has been very stable following replication in animals and humans (21). Nevertheless, recent studies on the genetic stability of FluMist reported that mutations can occur in the manufacturing process and in the replication of the virus in vaccinated children (40,41).…”
mentioning
confidence: 99%
“…Previously, the PA M431 amino acid of MDV-B had been shown to contribute to the control of the ts phenotype, but those studies concluded that other residues were also likely to contribute to expression and reversion of this trait (5,6). The findings reported here show that three amino acid loci of MDV-B-PA M431, NP A114, and NP H410-were the minimal elements that controlled the ts phenotype, and reversion of all three loci in combination was required to revert the ts phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…By using classical reassortment techniques, it was reported that the MDV-B PA gene segment could transfer the ts and att phenotypes to the heterologous B/Hong Kong/1732/76 strain (5,6). Mutation of methionine 431 to isoleucine in this reassortant reverted the ts phenotype (i.e., non-ts) of the virus, demonstrating the critical nature of M431.…”
mentioning
confidence: 99%